2009
DOI: 10.1016/s1130-1473(09)70159-9
|View full text |Cite
|
Sign up to set email alerts
|

Purely intramedullary spinal cord primitive neuroectodermal tumor: case report and review of the literature

Abstract: Introduction. Primitive neuroectodermal tumors (PNETs) are malign neoplasms of the central nervous system which mainly locate in cerebellum (medulloblastoma). Primary intraspinal PNETs are rare. Within this group, we have found ten cases of purely intramedullary PNETs (IPNETs). In this report, we describe a new IPNET case and review the literature about these infrequent intramedullary tumors.Case report. A 17 month-old boy showed progressive decrease of motion in his lower extremities. Spine magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 14 publications
0
19
0
5
Order By: Relevance
“…The history of clinical presentation was short ranging from 6 days to 8 weeks. 13) Our patient was a 39-year-old male with a lesion at the level of conus medullaris manifesting as rapid neurological deterioration for 2 weeks.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The history of clinical presentation was short ranging from 6 days to 8 weeks. 13) Our patient was a 39-year-old male with a lesion at the level of conus medullaris manifesting as rapid neurological deterioration for 2 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…1,3,8,9,12) Intramedullary PNET is even more rare and has been documented primarily as case presentations and short series. [4][5][6][7]13) Cauda equina syndrome refers to a constellation of symptoms that result from damage to the cauda equina. This syndrome may present as sciatica, low-back pain, saddle analgesia, decreased rectal tone, absent bulbocavernosus, patellar, and Achilles reflexes, bowel and bladder dysfunction, and lower extremity weakness.…”
Section: Introductionmentioning
confidence: 99%
“…11,13,19) Because of the confusion in classification and scarce clinical data for individual cases, the distinction between CNS PNET and pPNET has not always been made. Recently, attempted division of reported cases found 12 cases of CNS PNET and 17 cases of pPNET.…”
Section: Discussionmentioning
confidence: 99%
“…13) In addition, reviews of the literature found 7 and 11 cases of intramedullary CNS PNET. 11,19) We re-examined individual clinical data, CD99 expression, and genetic studies for these cases, and recognized 12 cases as definite primary intramedullary CNS PNETs ( Table 1). The present case is the 13th known case and the first to be evaluated by both immunohistochemistry and molecular Neurol Med Chir (Tokyo) 51, August, 2011 CNS PNET of the Spinal Cord analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation